[What factors determine the efficacy of histology learning in medical university?] - Sulaieva O.N. (Морфологія, 2015)
Current development of medicine determines the necessity to revise the content of the lessons and teaching tools in fundamental sciences including histology. In this paper the following issues are considered: 1. Use of the problembased education to stimulate clinical motivation and real interest of students to basic sciences including histology. 2. Reorganization of stuff administration to prepare highly qualified young teaches on histology. 3. Stimulation of associative and logic memory during histology studying. 4. Development of the positive educational milieu, including psychological comfort and satisfaction of the learning process and outcomes, as well as personalization of learning process. Citation: Sulaieva ON. [What factors determine the efficacy of histology learning in medical university?]. Morphologia. 2015;9(3):127-9. Russian.